PTU-050 The successful implementation of fast-track routine testing for microsatellite instability in a colorectal cancer pathway. (8th June 2018) - Ngu, Wee Sing; Mills, Sarah; Sheth, Harsh; Burn, John; Lee, Thomas
Abstract : Introduction: The National Institute for Health and Care guidelines (DG27, Feb 2017) recommend that all patients with colorectal cancer (CRC) should undergo testing for deficient deoxyribonucleic acid (DNA) mismatch repair activity, whose by-product is microsatellite instability (MSI) in DNA. Historically in our trust, MSI testing was done infrequently, in selected high-risk patients, on preserved pathology specimens and with a long wait for results. A new patient care pathway incorporating MSI testing on fresh biopsy tissue with a rapid turnaround time was introduced in January 2017. This service evaluation reviewed performance in the first year of this new pathway. Methods: Endoscopists were asked to send an additional fresh biopsy for MSI assay at endoscopic diagnosis of significant neoplasia from January 2017. Data for all patients newly diagnosed with CRC between 1 st Jan 2017 to 31 st December 2017 were exported from a prospectively populated database. Results: A total of 374 patients were identified, median age 72 (range 30–96) of whom 226 (60.4%) patients were diagnosed at endoscopy. One hundred and ninety-one (51.1%) of all patients had MSI assays performed, 142 (62.8%) of those endoscopically diagnosed. Twelve (6.3%) of the patients tested were MSI-high. Median time from submission of sample to result was 13 days (range 3–32). Conclusions: Compliance with MSI testing at endoscopic diagnosis is not yet 100%, but this study illustrates that the MSI test can be integrated into the patient care pathway in an NHS setting and used to personalise patient care as turn-around times are sufficiently short for the results to be integrated into pre and post-operative multidisciplinary team meeting discussions.